2013
DOI: 10.1094/mpmi-03-13-0064-r
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of the NADPH Oxidase Complex in the Ergot Fungus Claviceps purpurea: CpNox2 and CpPls1 Are Important for a Balanced Host-Pathogen Interaction

Abstract: Reactive oxygen species producing NADPH oxidase (Nox) complexes are involved in defense reactions in animals and plants while they trigger infection-related processes in pathogenic fungi. Knowledge about the composition and localization of these complexes in fungi is limited; potential components identified thus far include two to three catalytical subunits, a regulatory subunit (NoxR), the GTPase Rac, the scaffold protein Bem1, and a tetraspanin-like membrane protein (Pls1). We showed that, in the biotrophic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 73 publications
1
28
0
1
Order By: Relevance
“…In addition, the CpDock180 localization at the plasma membrane corresponds with the predicted association of active GTPases with the plasma membrane and could represent the recruitment and subsequent activation of GTPases at the cell periphery. A similar vesicle localization has been observed for CpNoxR and NoxR of B. cinerea (88; D. Buttermann and P. Tudzynski, unpublished data), further strengthening the close connection between Rac and Nox signaling in C. purpurea (47). Another hint for the cross talk between CpRac and Nox signaling is the interaction of the regulatory Nox protein CpNoxR with CpCdc24 and CpDock180.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…In addition, the CpDock180 localization at the plasma membrane corresponds with the predicted association of active GTPases with the plasma membrane and could represent the recruitment and subsequent activation of GTPases at the cell periphery. A similar vesicle localization has been observed for CpNoxR and NoxR of B. cinerea (88; D. Buttermann and P. Tudzynski, unpublished data), further strengthening the close connection between Rac and Nox signaling in C. purpurea (47). Another hint for the cross talk between CpRac and Nox signaling is the interaction of the regulatory Nox protein CpNoxR with CpCdc24 and CpDock180.…”
Section: Discussionsupporting
confidence: 78%
“…The interaction of NoxR and Cdc24 occurs similarly in E. festucae (32) and is mediated by the type I PB1 domain in CpCdc24 and the type I/II PB1 domain in CpNoxR. We recently showed that CpNoxR is able to interact with Rac, in a loading-status-dependent manner, and binds to CpBem1 (47). All these characteristics indicate a role of CpNoxR as another type of downstream effector of CpRac.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations